Interleukin-6 and delayed onset muscle soreness do not vary during the menstrual cycle - Chaffin, M. E.; Berg, K. E.; Meendering, J. R.; Llewellyn, T. L.; French, J. A.; Davis, J. E. (Research Quarterly for Exercise and Sport, 2011)
The purpose of this study was to determine if a difference in interleukin-6 (IL-6) and delayed onset muscles soreness (DOMS) exists in two different phases of the menstrual cycle. Nine runners performed one 75-min high-intensity interval running session during the early follicular (EF) phase and once during the midluteal (ML) phase of the menstrual cycle. Estrogen and progesterone levels were significantly reduced in the EF phase when compared to the ML phase. IL-6 levels increased from pre- to postexercise in the EF and ML phases (p < .001). There was no relationship between the IL-6 level and DOMS. The results suggest that menstruating female runners need not vary training throughout the month to reduce DOMS.